HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KEMAMPUAN SHOOTING PEMAIN SEPAK BOLA CLUB BIMANUSA TANJUNG MEDANG KABUPATEN KEPULAUAN MERANTI - Nur Asikin; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, type of research is Koreasional who want to see the relationship between the two variables of leg muscle explosive power with the ability shotting on football Players Club Bimanusa Cape Medang. Explosive power leg muscle as independent variables and the ability shotting as the dependent variable. The population in this study was Footballer Club Bimanusa Cape Medang aged 16-19 years were enrolled active training totaling 28 people at the same time be made in the sample (total sampling), data retrieval technique was measured by a meter, the second is a test shooting who performed the mouth of the goal, a data analysis technique is a simple correlation (Product Moment). The hypothesis of the research results obtained showed explosive power leg muscle (x) does not have a significant relationship and did not contribute significantly to the ability shotting (y), P = 0.524 α. relationship leg muscle explosive power and ability shotting worth 0.126 <0.374 r tab thus proposed a working hypothesis (Ha) is rejected. Thus it can be concluded that there is no significant relationship between the explosive power leg muscle with shooting ability on the football Players Club Bimanusa Cape Medang age of 16-19 years.Keywords : Explosive Power of leg powe, shooting